Towards Health in All Policies for Childhood Obesity Prevention - Anna-Marie Hendriks; Stef P. J. Kremers; Jessica S. Gubbels; Hein Raat; Nanne K. de Vries; Maria W. J. Jansen (Journal of Obesity)
The childhood obesity epidemic can be best tackled by means of an integrated approach, which is enabled by integrated public health policies, or Health in All Policies. Integrated policies are developed through intersectoral collaboration between local government policy makers from health and nonhealth sectors. Such intersectoral collaboration has been proved to be difficult. In this study, we investigated which resources influence intersectoral collaboration. The behavior change wheel framework was used to categorize motivation-, capability-, and opportunity-related resources for intersectoral collaboration. In-depth interviews were held with eight officials representing 10 non-health policy sectors within a local government. Results showed that health and non-health policy sectors did not share policy goals, which decreased motivation for intersectoral collaboration. Awareness of the linkage between health and nonhealth policy sectors was limited, and management was not involved in creating such awareness, which reduced the capability for intersectoral collaboration. Insufficient organizational resources and structures reduced opportunities for intersectoral collaboration. To stimulate intersectoral collaboration to prevent childhood obesity, we recommend that public health professionals should reframe health goals in the terminology of nonhealth policy sectors, that municipal department managers should increase awareness of public health in non-health policy sectors, and that flatter organizational structures should be established.